Properties of Hollow Sandcrete Blocks Produced from Ultrafine Carbon Particles Blended Cement (2023)
This study investigated the properties of hollow sandcrete blocks produced from ultrafine carbon particles (UCP) blended cement. Waste radio batteries were obtained from electronic repairers and dumpsites in Osogbo. The carbon rod in the batteries were sorted and mechanically grinded to UCP. The UCP replacement levels of 1, 2, 3, 4 and 5% were used. A total of 36 hollow sandcrete block specimens of dimension 450 × 225 × 150 mm were cast using mix ratio 1:5 to undergo density, water absorption and compressive strength tests at 7 and 28 days of curing respectively. The densities of the control, 1, 2, 3, 4 and 5% UCP were 1136, 1169, 1152, 1158, 1154 and 1152 kg/m3 at day 7, and 1063, 1093, 1106, 1128, 1134 and 1142 kg/m3 at day 28 respectively. Their respective water absorption were 6.0, 5.3, 5.0, 3.0, 2.8 and 2.0% at day 7 and 12.0, 10.0, 7.0, 6.0, 5.0 and 2.4% at day 28. The water absorption for all the mixtures were within the BS specification of 12% maximum. The 28 day compressive strength increased by 15.48, 19.01, 25.26, 20.52 and 16.47% for 1, 2, 3, 4 and 5% UCP replacement respectively. It is concluded that UCP can be used to improve the compressive strength of sandcrete blocks at acceptable density and water absorption.